Designing Strategies using IFE, EFE, IE, and QSPM analysis: Digital Village Case - Alamanda, Dini Turipanam; Anggadwita, Grisna; Raynaldi, Mochammad; Novani, Santi; Kijima, Kyoichi (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. Digital SMEs Village is a program initiated by Telekomunikasi Indonesia. The program is expected to grow entrepreneurial spirit among business actors, as well as to facilitate business actors to expand their business network by utilizing technological developments in Indonesia. The common problem of Digital SMEs Village Indonesia today is the number of human resources that still lack the understanding of using smartphones and computers to interact with consumers in cyberspace. One of the Digital SMEs Village in Bandung district is the Baraya Digital SMEs Village. This study aims to identify the formulation strategy in the development of the Baraya Digital SMEs Village by SWOT analysis. Furthermore, Quantitative Strategies Planning Matrix (QSPM) is used to decide and determine which alternative strategies can best be recommended. The research method used is qualitative method with case study approach by doing depth-interview to several key actors in the Baraya Digital SMEs Village. The results showed that the Baraya Digital SMEs Village needs to implement intensive strategy. The development of strategies that need to be implemented as a top priority is market penetration, by expanding the market share of existing products through online marketing.Keywords:Â  Digital SMEs Village, cyberspace, SWOT Analysis, QSPM